New insights into restrained stress and deformation mechanisms of concretes blended with calcium sulfoaluminate and MgO expansive additives using multi-scale techniques. (31st March 2023) - Ou, Guangfeng; Kishi, Toshiharu; Mo, Liwu; Lin, Zhihai
Highlights: Temperature stress testing machine is used to evaluate cracking performance. MgO additives compensate shrinkage better than CSA under high temperature. CSA additives show much greater creep effect than MgO under high temperature. MgO additives reveal better resistance to shrinkage than CSA in wetting–drying cycles. CSA sample shows a coarser pore structure with less ink-bottle pores than MgO. Abstract: The early-age cracking performance of expansive concrete relies heavily on the temperature, restraint and curing conditions. Empirical methods to use expansive additives are not always reliable in diverse engineering conditions. By using a novel approach with the self-developed temperature stress testing machine (TSTM), this study evaluates the early-age cracking sensitivity of concretes blended with Calcium Sulfoaluminate and MgO expansive additives under different engineering conditions. Their performances under wetting–drying cycles are also compared. To interpret the deformation mechanism in a microscopic scale, pore structures are characterized by mercury intrusion porosimetry and nitrogen adsorption/desorption tests. It is found that MgO concrete with proper reaction activity can offer more effective shrinkage-compensation effect than CSA concretes under high temperature or drying condition, due to its less demand for hydration water, delayed expansion and finer pore structure. The findings in this study offer us new insights in modelling and application of expansive concretes on site.